Reproductive activity and spatial behavior of common voles (Microtus arvalis Pallas, 1778) in response to simulated mustelid predation risk - Jochym, Mateusz (2012)
Arvicoline rodents adapt to predation risk imposed by specialist predators (e.g. mustelids) in several ways. These include breeding suppression as well as changes in spatial and temporal activity. I investigated whether such adaptations are employed by common voles (Microtus arvalis). Breeding suppression hypothesis (BSH) predicts that females will suppress breeding in response to high risk of mustelid predation, thus gaining higher chances of survival. I used capture-mark-recapture data to verify whether breeding suppression occurs in M. arvalis, and how population density combined with predation risk affects voles' reproductive activity. In contrast to males, some females did suppress breeding; this confirmed the BSH. A model of the interaction between predation risk and population density revealed that response to predation risk depends on the density of conspecifics: breeding suppression is a viable adaptation only at low vole densities. Despite predation risk, some females maintained reproduction. To establish whether they responded at all, I measured two parameters of their reproductive output: the number of recruits per litter, and the interval between litters. The number of recruits per litter was not affected, but litters of females facing predation risk were less frequent. This indicates that the effect of predation risk on females is more complex than originally proposed: while some females suppress breeding, the frequency of litters is affected in others. This effect may be linked with regulation of estrus. Spatial and temporal activity of breeding females was measured using radio-tracking. Size of activity range, movement distances and temporal behavior were not influenced by predation risk. However, the females clearly avoided the sources of mustelid odor. Reproductively active females cannot afford spatial and temporal adaptations, as these limit foraging opportunities and ultimately, fecundity. Yet, they respond to predator odors.